Saving the wild South the fight for wild plants on the brink of extinction - Eubanks, Georgann (The University of North Carolina Press, 2021)
"From the Miccosukee gooseberry to the Florida torreya, the twelve plants starring in The wild South are native to the American South, a place known for its astonishingly rich biodiversity. Georgann Eubanks treks across the region, from Alabama to North Carolina, reporting on their wondrous biology. But these plants are in dire trouble-each one is struggling to survive against the effects of global climate change and disruptive development. Ten of them have already been granted federally endangered status"--